2015
DOI: 10.1126/science.1261412
|View full text |Cite
|
Sign up to set email alerts
|

Universal solvent restructuring induced by colloidal nanoparticles

Abstract: Colloidal nanoparticles, used for applications from catalysis and energy applications to cosmetics, are typically embedded in matrixes or dispersed in solutions. The entire particle surface, which is where reactions are expected to occur, is thus exposed. Here, we show with x-ray pair distribution function analysis that polar and nonpolar solvents universally restructure around nanoparticles. Layers of enhanced order exist with a thickness influenced by the molecule size and up to 2 nanometers beyond the nanop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
205
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(233 citation statements)
references
References 32 publications
14
205
1
Order By: Relevance
“…This presumably arose from the markedly different microenvironment found in the localized QD-PTE hydration layer. Supporting this notion, a recent report confirms that structural rearrangement of the localized environment around colloidal NPs is a universal phenomenon regardless of what the actual solvent is [16]. We have even found a significant enhancement when working with the large multimeric β-galactosidase enzyme and QDs [17].…”
supporting
confidence: 81%
“…This presumably arose from the markedly different microenvironment found in the localized QD-PTE hydration layer. Supporting this notion, a recent report confirms that structural rearrangement of the localized environment around colloidal NPs is a universal phenomenon regardless of what the actual solvent is [16]. We have even found a significant enhancement when working with the large multimeric β-galactosidase enzyme and QDs [17].…”
supporting
confidence: 81%
“…Indeed, a recent X-ray pair distribution function analysis study suggested that such enhanced short-range order of organic molecules, both polar and nonpolar, induced by colloidal NPs is universal. The restructuring effect may reach up to 2 nm beyond the particle surface and directly contribute to the functionality of NPs (34).…”
Section: Discussionmentioning
confidence: 99%
“…291,297 Notably, the solvent shells were found to be up to four times the density of the bulk solvent; similarly, dense solvation shells have been measured for a range of other nanoparticles in different solvents. 410 Furthermore, for the fulleride dispersions, the polar moment of the solvating ammonia molecules did not point toward the C 60 anions, rather tangentially with only one H atom per ammonia molecule directed to the fullerides. 291,297 This counterintuitive arrangement enables the ammonia molecules within the solvation shells to maintain the hydrogen-bonding arrangement found in bulk ammonia.…”
Section: Polyelectrolyte Theory For Ccnsmentioning
confidence: 99%